2019
DOI: 10.1186/s43014-019-0002-7
|View full text |Cite
|
Sign up to set email alerts
|

The relevance of dipeptides and tripeptides in the bioactivity and taste of dry-cured ham

Abstract: Dry-cured ham has been described as a good source of bioactive peptides and taste-active compounds. Some of them are dipeptides and tripeptides that are released in a large amount from different muscle proteins due to the action of exopeptidases during the dry-cured ham processing. The potential of dipeptides and tripeptides to exert bioactivities and impart taste characteristics to dry-cured ham has been evaluated using the BIOPEP database, since in silico approaches are a time-and cost-effective alternative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 86 publications
1
40
0
Order By: Relevance
“…This strategy of research based on searching for biopeptides with known sequences in the protein that so far had not been known as their source is called a positive selection. Such an idea to study biopeptides from foods was applied by several authors [45,46,[49][50][51]. Thus, the next step in our study was to acquire the information about the peptides theoretically found in peptic and/or tryptic hydrolysates of collagens.…”
Section: Source Of Collagenmentioning
confidence: 99%
“…This strategy of research based on searching for biopeptides with known sequences in the protein that so far had not been known as their source is called a positive selection. Such an idea to study biopeptides from foods was applied by several authors [45,46,[49][50][51]. Thus, the next step in our study was to acquire the information about the peptides theoretically found in peptic and/or tryptic hydrolysates of collagens.…”
Section: Source Of Collagenmentioning
confidence: 99%
“…These new methods involve also bioinformatic analyses. According to Gallego et al [2019], the bioinformatic-assisted approach affords the opportunity to predict the production of bitter peptides from food sources in a cheaper and faster way. Our idea of employing predictive (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, in silico studies combined with empirical methodologies enable the complete search for tasting-peptides derived from foods. However, all theoretical predictions of food taste must be confi rmed [Gallego et al, 2019].…”
Section: Resultsmentioning
confidence: 99%
“…This helps understanding some relationships between the structure of a molecule and its activity (e.g., bitter taste). It needs to be noted that although it is possible to prognose the potential of released peptides to taste bitter, such a statement should be confirmed in laboratory conditions [70].…”
Section: Discussionmentioning
confidence: 99%